Specific or not specific recruitment of DNMTs for DNA methylation, an epigenetic dilemma - Hervouet, Eric; Peixoto, Paul; Delage-Mourroux, Régis; Boyer-Guittaut, Michaël; Cartron, Pierre-François (Clinical epigenetics, 2018)
Our current view of DNA methylation processes is strongly moving: First, even if it was generally admitted that DNMT3A and DNMT3B are associated with de novo methylation and DNMT1 is associated with inheritance DNA methylation, these distinctions are now not so clear. Secondly, since one decade, many partners of DNMTs have been involved in both the regulation of DNA methylation activity and DNMT recruitment on DNA. The high diversity of interactions and the combination of these interactions let us to subclass the different DNMT-including complexes. For example, the DNMT3L/DNMT3A complex is mainly related to de novo DNA methylation in embryonic states, whereas the DNMT1/PCNA/UHRF1 complex is required for maintaining global DNA methylation following DNA replication. On the opposite to these unspecific DNA methylation machineries (no preferential DNA sequence), some recently identified DNMT-including complexes are recruited on specific DNA sequences. The coexistence of both types of DNA methylation (un/specific) suggests a close cooperation and an orchestration between these systems to maintain genome and epigenome integrities. Deregulation of these systems can lead to pathologic disorders.